Experimental and numerical investigation of smoke dynamics in vertical cylinders and open-air environment. (June 2019) - Ahn, Chan-Sol; Park, Chan-Woo; Kim, Min-Woo; Kim, Tae-Gun; James, Scott C.; Yoon, Youngbin; Yarin, Alexander L.; Yoon, Sam S.
Highlights: Small-scale experiments were performed to measure smoke rise in 2-m cylinders. For narrowest cylinder, smoke velocity decreased due to the boundary-layer thickness. For narrowest cylinder, the axial velocity became fully developed toward the top. The analytical and numerical results were compared against experimental data. Abstract: Smoke rise in elevator shafts and stairwells is a primary risk from fires. Information on temperature and smoke velocity is necessary for safety evaluation and evacuation guidelines when designing high-rise buildings. Small-scale experiments were performed to measure smoke rise in open-ended, 2-m cylinders with diameters D  = 1, 0.5, and 0.14 m and heating powers Qz  = 32, 144, and 220 W. When D  ≥ 0.5 m, smoke characteristics resembled those under open-air conditions for all values of Qz with minor deviations. When D  = 0.14 m, smoke velocity decreased due to the increased relative boundary-layer thickness. For this narrowest cylinder, smoke temperature also decreased because of the relative increase of cool air drawn through the cylinder bottom. The overall mass flow rate was lowest through the smallest cylinder because of the reduced axial velocity and cross-sectional diameter. The axial velocity became fully developed toward the cylinder top; however, the velocity decreased again when the smoke exited. Temperature distributions were also uniform at the cylinder outlet because of the fully developed flow field. Increase in Qz increased temperature and velocity for all cylinders. Both the analytical solution from the open-air plume theory and numerical simulations using Fire Dynamics Simulator were compared against experimental data.